Listening to Mozart - Wyatt, Charles, 1943- (John Simmons short fiction award., 1995)
Twelve stories on life as seen by a flute player. He is James Wallace of Nashville, 40, an enterprising 1960s anti-war hippie who instead of going to Canada joined the U.S. Marine Corps as a bandsman and avoided the war that way.